ANALISIS VALIDITAS MEDIA MOVABLE BOOK UNTUK MENGEMBANGKAN BAHASA AUD - Firdausi Nuzula Apriliyana (Program Studi PG PAUD Universitas PGRI Ronggolawe, 2022)
The type of this research is development research that produces Movable Book media products. The purpose of this study was to determine the feasibility of Movable Book media to stimulate language skills in children aged 5-6 years at Baiturrohman Kindergarten, Wangun Village, Palang District, Tuban Regency. This study uses the Research and Development (R&D) method which refers to the 4-D development model. The 4-D development model includes 4 stages, namely defining or defining, planning or design, developing or developing, and disseminating. In the process of collecting data, the researcher used a closed questionnaire which was submitted to the validators as experts. The validators involved in this study were five people consisting of two material experts and three media experts. There is no field test for students due to the COVID-19 pandemic which causes no teaching and learning activities in educational institutions. The subjects of this study were the five validators. Meanwhile, the object of this research is the Movable Book media. Based on the results of data analysis obtained from the validators, the results obtained from material experts are 76% with the criteria of